ISPO Implementation at PT Surya Mata Ie Plantation: Challenges & Opportunities for Sustainable Certification - Muamar Hafizh; Lithia Lutfi Widari (Program Pascasarjana UIN Sumatera Utara, 2025)
The implementation of the Indonesian Sustainable Palm Oil (ISPO) is a strategic step to improve the sustainability of the palm oil industry in Indonesia. This article examines the challenges and opportunities in ISPO implementation at PT Surya Mata Ie, a palm oil plantation company located in Aceh. The research method used is a case study with a qualitative approach, involving in-depth interviews, document analysis, and field observations. The results show that the main challenges of ISPO implementation include limited resources, internal resistance, and regulatory bureaucracy. However, significant opportunities such as increased competitiveness in the global market, operational efficiency, and strengthened corporate reputation were also identified. The article concludes that successful implementation of ISPO requires collaboration across stakeholders and innovation in plantation management.